(untitled) (Journal of the Sociology and Theory of Religion, 2012)
Globalization and new consumption patterns influence daily life, the postmodern human being livesan existencial angst, the awareness of living here and now, in a violent and hostile world, thestruggle for survival after the basic needs. Given this, options or alternatives present themselves asa way of life. Sociological changes of globalization include religions, we can mention thephenomenon of transnational and transcontinental networks.In Argentina, particularly Buenos Aires as the case observed, is considered a religious metropoliwhere different offers coexist: the Catholic healing circuit including San Cayetano, San Pantaleonand the Virgin “Desatanudos”; St. Expedite, charismatic healers, electronic ministers, rabbis, Islamic,Hindus, Buddhists, schools of spirituality, new age, indigenous healers, “manosantas” (healinghands), holistic therapies, tarot, parapsychology, etc.The mapping of religious groups in the city of Buenos Aires highlights some areas such as Almagro,in the geographic center of the city, and Liniers on the western edge with the Church of SanCayetano and the burgeoning Bolivian community.This paper addresses the case study of the neighborhoods mentioned and the opinions of experts onthe subject of sociology.